The Best Part of Life : Subsistence Hunting, Ethnicity, and Economic Adaptation among Young Adult Inuit Males - Condon, Richard G.; Collings, Peter; Wenzel, George (ARCTIC, 1995)
This paper examines the economic adaptations and subsistence hunting involvement of households between the ages of 20 and 35 in the Copper Inuit community of Holman. Social, economic, and political changes throughout the Canadian Arctic have made it impossible for young adults to pursue the same mixed economic strategies as previous generations. A general decrease in subsistence hunting involvement is characteristic of the younger generation. Nevertheless, some young householders have made a conscious effort to remain active in subsistence hunting and fishing to provide for themselves and related households. Some have even increased subsistence hunting involvement as their own parents age and become increasingly infirm. Other householders are less active in hunting and fishing, but continue to view land-based harvesting as central to a sense of Inuit identity. The motivations, economic position, and family background of a sample of active and less active young adult hunters are explored in an attempt to understand the pressures experienced by young adults as they strive to make a place in a northern society radically different from that of their parents at a similar age. While the authors recognize the economic value of subsistence harvesting and the foods that result from it, we also emphasize the less easily quantified dimensions of subsistence ideology and its impact upon physical health, psychological well-being, and community integration.Key words: subsistence, harvest effort, Inuit identity, young adults, food sharing, health, self-esteem Cet article examine les adaptations économiques et l'activité de chasse de subsistance de chefs de ménage âgés de 20 à 35 ans, dans la communauté Copper Inuit de Holman. Les changements sociaux, économiques et politiques qui ont eu lieu dans tout l'Arctique canadien ont fait qu'il est impossible pour les jeunes adultes de poursuivre les mêmes stratégies d'économie mixte que les générations précédentes. La génération la plus jeune se caractérise par une diminution ...